Protein export and membrane biogenesis - Dalbey, Ross E. (Advances in cell and molecular biology of membranes and organelles, 1995)
The incentive for putting together Volume 4 of this series was to review the wealth of new information that has become available in prokaryotic organisms in protein export and membrane biogenesis. Just in the last several years, protein translocation has now been efficiently reconstituted using defined components and the mechanism by which proteins are moved across membrane bilayers is now being examined at a higher resolution. In addition, because of a new technical breakthrough using osmolytes, it is now possible to reconstitute a number of channel proteins, ATPase, receptors, and transporters. In many cases, it is possible to successfully predict the membrane topology of these types of proteins using both "hydrophobicity analysis" and the "positive inside" rule.